A STUDY OF INDONESIAN SLANG IN TWO LUPUS MOVIES - Marwa, Annisa Friski (2016)
This study aims to investigate the Indonesian Slang used in the two Indonesian movies, entitled Lupus and to reveal the commonalities and differences of Slang usage in the different time slot movies. The data are the spoken slang in the two movies; Lupus: Kejar Daku Kau Kujitak (1987) and Bangun lagi dong Lupus! (2013). Furthermore, the data are classified into Mattielo's (2008) types of slang and O'Grady and Guzman's (1996) word-formation theories, complemented by Hatch and Brown's (1995) to seek the commonalities and differences of the slang. The findings reveal that the types of slang in both movies are age and localism restricted type and unconventionality type. In addition, the word formation process of slang that mostly occurrs are borrowing, clipping, affixation in Lupus 1987 and borrowing, affixation and coinage in Lupus 2013. In conclusion, Indonesian slang, according to its speakers and its functions, is still mostly used by teenagers and identical with Betawinese, a regional language. In contrast, due to the time difference of the movie, the development of information and technology influences slang used in the latest movie, especially borrowing English, and the slang is also enriched by many new term creations. ;---Penelitian ini bertujuan untuk meneliti penggunaan slang bahasa Indonesia di dalam dua film, berjudul Lupus, dan untuk mengungkapkan persamaan dan perbedaan penggunaan slang bahasa Indonesia di dalam film yang berbeda masa. Data penelitian merupakan slang yang diucapkan di dalam dua film; Lupus: Tangkaplah Daku, Kau Kujitak (1987) and Bangun lagi dong Lupus! (2013). Kemudian diklasifikasikan ke dalam jenis slang teori Mattielo (2008) dan pembentukkan kata teori O'Grady dan Guzman (1996) dilengkapi oleh teori Hatch dan Brown (1995) untuk mencari persamaan dan perbedaannya. Temuan mengungkapkan bahwa jenis slang di kedua film adalah tipe age and localism restricted "terbatas pada usia dan domisili" dan jenis unconventionality "inkonvensional". Sebagai tambahan, pembentukkan kata yang paling sering muncul adalah, borrowing, clipping dan affixation di dalam film Lupus 1987 dan borrowing, affixation, dan coinage di dalam film Lupus 2013. Kesimpulannya, slang bahasa Indonesia menurut penutur dan fungsinya kebanyakan masih digunakan oleh remaja dan identik dengan dialek Betawi. Sebaliknya, dengan adanya perbedaan waktu diantara kedua film, perkembangan informasi dan teknologi mempengaruhi pengguanaan slang pada film terbaru, khususnya penyerapan bahasa Inggris dan slang juga diperkaya dengan banyaknya kreasi istilah baru.